Intrasellar pituitary mucocele: Diagnostic dilemma. (June 2014) - Tang, Ing Ping; Chai, Chun Kian; Kumar, Gnana; Prepageran, Narayanan; Waran, Vicknes
Abstract Isolated intrasellar pituitary mucocele following transsphenoidal sinus surgery is extremely rare. The clinical features resemble a pituitary tumor, therefore careful radiological interpretation is crucial to reach the correct diagnosis. We report a case of intrasellar mucocele who had transsphenoidal sinus surgery performed 15 years prior.